ANALISIS RANCANGAN PERBAIKAN DESIGN MOLD DENGAN MENGGUNAKAN METODE TAGUCHI DI PT X - Yani Iriani; Sri Lestari; Riki Ridwan Margana; Irfan Rifai (LPPM Universitas Bina Bangsa, 2023)
PT X Indonesia is one of the Korean Foreign Manufacturing Companies (PMA) that produce injection molding. December 2022 PT X Indonesia received customer complaints from PT. Y because of defects in products such as: gas burn, white spot, weld line, bending, short shoot, bubbles, flashing, silver, wrong color, and contamination. Flashing is a type of defect that the largest number of ratios reaches 10% while the defect restriction of the customer is 2% so the company and the authors choose the theme of improvement in 2018 is the improvement of molding design to reduce flashing defects in plastic products. The method used in the proposed improvement of molding design is the taguchi method by making 4 point suggestion that is the level 1 slot dimension: Hight 70mm taper 15 °, level 2: Hight 70mm taper 10 °, level 3: High 70mm taper 5 °; insert level 1 dimension: 70mm taper insert 1 °, level 2: 70mm taper deepness insert 2 °, level 3: 70mm taper deepth insert 3 °; clamping tolerance force level 1: + 5%, level 2: + 8%, level 3: + 10% and parting line line length 1: 10mm, level 2: 20mm, level 3: 30mm. The proposed best molding design improvements are in Slast dimensions: Hight 70 mm taper 15 °, Insert: 70mm taper deepness 2 °, clamping force tolerance + 10%, Parting Line Length: 30mm. The smallest flashing flaw was found to be 0.1% in confirmatory experimental conditions, much smaller than the specified target defects of 2%. Cost reduction cost obtained by PT ART Mold Indonesia with the proposed repair on Molding design that is Rp 115.600.000,00 per 1 molding. The cost savings incurred by customers of PT ART Mold Indonesia is worth Rp 784.080.000,00 per year